Factors Influencing Relapse Among Male Adolescent Opium Addicts In Kerman, Iran - Golestan, Samira (2009)

(untitled)
This study was designed to determine factors influencing relapse among male adolescent opium users. The main purpose of this study was to examine the relationship between family factors, environmental factors and also individual factors (self-esteem and life skill) on relapse in male adolescence opium users. The specific objectives of the study were: first, to describe the profile characteristics of male adolescents opium users, second is to examine the relationship between family, environmental and individual factors (self-esteem and life skills) on relapse in male adolescent opium users and third to identify which factors contribute most to relapse in male adolescent opium users in Kerman. A quantitative research method was employed. The total population of the study included all opium addicted adolescents between the ages of 13 to 20 who had relapsed. In this study the available population identified was the opium addicted adolescents between the ages of 13 to 20 who at least once had relapsed after treatment and was referred to rehabilitation centres in 2009 in Kerman. Two hundred twenty six male adolescent opium addicts between the ages of 13 to 20 years who suffered relapse after treatment in Kerman participated in this study. This study measured four dimensions, used to measure the factors influencing relapse which include family factors, environment factors as well as individual factors, namely self-esteem and life skills. Information for this study was derived from selfadministered questionnaires. Descriptive analysis and inferential statistics such as Pearson Correlations Coefficient test and Stepwise Regression were used to examine the relationship between family factors, environmental factors and individual factors (self-esteem and life skills) with relapse and also to identify which factors contribute the most to relapse. Descriptive statistics were used to describe the level of respondents‟ personal background, as well as to describe the key study variables: family factors, environmental factors, individual factors and relapse. The findings indicated that 48.7% of the respondents regarded family factors as highly important in their relapse and also 46% showed high effects of environmental factors on their relapse as well as the findings revealed that a majority of the respondents (76.5%) indicated a low level of individual factors (self-esteem) and 78.8% showed a low level of life skills. Furthermore, 56.6% of the respondents had relapsed after treatment. The findings from correlations showed that, there were significant correlations between three factors with relapse in adolescents. That is a significant moderate positive relationship between family factors and relapse (r=.315, p<0.01), and a significant moderate positive relationship between environmental factors and relapse (r=.323, p<0.01) were observed. In addition, there were significant moderate negative relationships between individual factors; i.e. self-esteem and relapse (r= -.328, p<0.01) and life skills and relapse (r= -.453, p<0.01).